Green synthesis of α-amino phosphonates using cassia fistula fruit pulp: Dual α-amylase and α-glucosidase inhibitors - Sankar, Arigala Uma Ravi; Khalivulla, Shaik Ibrahim; Chethana, Garivi; Kumar, Althurthi Bharani Venkata Kiran; Chaitanya, Matcha (International Journal of Chemistry and Materials Research, 2026)
Diabetes is largely developing in the human population due to modern and sedentary lifestyles, leading to serious health complications that affect nerves, eyes, and kidneys. Organophosphorus compounds have diverse pharmacological properties, including antidiabetic properties. In the recent literature, α-aminophosphonates were prepared by green synthesis using orange peel as a biocatalyst. In the current study, we have prepared the same compounds via Pudovik reaction using substituted aromatic aldehydes, aniline, and diethyl phosphite with Cassia fistula fruit pulp (CFFP) as a natural catalyst under reflux. The reaction mechanisms of imine (Schiff’s base) formation and Pudovik reaction products (5a-5h) were presented. Their antidiabetic potential was evaluated through molecular docking and in vitro studies against α-amylase and α-glucosidase. Notably, the compounds 5f, 5e, and 5d showed strong dual inhibitory activity with binding energies of -6.7848, -6.7843 and -6.7598 KCal/Mol, respectively, for 1B2Y and, -9792, -6.8492 and -6.808 KCal/Mol, respectively, for 5NN8 at active site residues; similarly, for in vitro studies the compounds exhibited inhibitory activity against IC50 values 0.75, 2.17, 4.51 µg/ml, respectively, for α-amylase and, 0.38, 1.81, 3.76 µg/ml, respectively, for α-glucosidase enzymes. Among these are also compounds 5f, indicating promising antidiabetic lead compounds, warranting further drug development studies for a therapeutic candidate. This study contributes to the existing literature by introducing CFFP as a novel, natural catalyst for the Pudovik synthesis of α-aminophosphonates and providing comprehensive dual inhibitory antidiabetic data against α-amylase and α-glucosidase.